Mediating effect of social support on the associations between health literacy, productive aging, and self-rated health among elderly Chinese adults in a newly urbanized community - Yang, Yikai (Medicine (Baltimore), 2019)
With the growing urbanization of China, which has changed older adults’ living conditions, lifestyle, and the source of support, coupled with rapid population aging, the health status of the elderly should be paid attention to. In addition to objective indicators such as the decline of function, specific factors, such as social support, health literacy, and productive aging, also have an impact on the health outcomes of the elderly. However, the interrelationships among these factors and their potential mechanisms in the context of urbanization remain unclear. Thus, this study was the first to explore the interrelationships among social support, health literacy, productive aging, and self-rated health in older adults living in a newly urbanized community in China. We aimed to investigate the mediating effect of social support on the associations between health literacy, productive aging, and self-rated health among elderly Chinese adults in a newly urbanized community to provide reference data for future health interventions for the elderly. This cross-sectional study was conducted between June and August 2013. Questionnaires on social support, health literacy, productive aging, and self-rated health were administered to 992 elderly residents. Structural equation models were used to examine the relationships among these 4 variables. Statistical analyses were performed using IBM SPSS Statistics 21.0 and Mplus 7.0. The mean scores for social support, health literacy, productive aging, and self-rated health were 34.5 ± 5.8, 13.6 ± 4.4, 11.3 ± 3.0, and 3.4 ± 0.7, respectively. Social support was directly related to self-rated health (β=0.119, 95% confidence interval [CI]: 0.041–0.198), while productive aging and health literacy had indirect associations with self-rated health via social support (β=0.071, 95% CI: 0.054–0.216; β=0.049, 95% CI: 0.066–0.183). Both productive aging (β=0.214, 95% CI: 0.047–0.381) and health literacy had direct associations with social support (β=0.327, 95% CI: 0.175–0.479), while health literacy had a direct association with productive aging (β=0.676, 95% CI: 0.604–0.748). Productive aging mediated the relationship between health literacy and social support. Overall, improving health outcomes among older adults requires enhancement of social support, along with consideration of productive aging and health literacy.